(3GdJbhjeGf GdgLQj hGdejdGOj (B/ s - (3LQfajd, aQjeGf s; (3GdGdhSj, MSGe eMj GdOjf s ((3HZOGO,GdYQGb (B: s (3OGQ GdTDhf GdKbGajI GdYGeI,s, 1986)
(3jbOe eDda gPG GdcJGH aQjeGf LQfajd WQjbI HSjWI hObjbI deYQaI GdJGQjN GdejdGOj GdebGHd dGj JGQjN gLQj hHGdYcS(B.s
(3GdfU HGddZI GdYQHjI eJQLe ef GddZI GdGfcdjRjI(B.s
Keywords: (3GdJbGhjes